Assessment of Zooplankton Diversity in Kosavampatti Lake at Namakkal District, Tamil Nadu: Assessment of Zooplankton Diversity in Kosavampatti Lake at Namakkal District, Tamil Nadu - Banu, G. Sharmila (International Journal of Pharmaceutical & Biological Archive, 2019)
Kosavampatti Lake is a historical lake situated in Namakkal district. A lake usually helps in recharging groundwater, and the trees in and around the lake serve as a nesting place for birds. Zooplankton is the vital constituents of water flora which aids as the main component of the aquatic food chain. It sustains appropriate equilibrium between biotic and abiotic components of the water ecosystem. The present study aimed to deal with zooplankton diversity in Kosavampatti Lake. The investigation was carried out for 1 year, i.e., October 2017–September 2018. During the study period, the zooplankton population of Kosavampatti Lake water is characterized by five various classes, namely Protozoa, Cladocera, Copepoda, Ostracods, and Rotifera, with 19 different species which were noted and documented in Kosavampatti Lake. The main classes of Rotifera are the highest groups among zooplankton and the density of zooplankton community was higher in summer and lesser in monsoon. The results of various kinds of diversity indices strongly indicate that Kosavampatti Lake is absolutely polluted in nature.